2023
DOI: 10.1007/s40618-023-02048-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and prognosis of COVID-19 in older adults with hypothyroidism: data from the GeroCovid observational study

Abstract: Background The prevalence of hypothyroidism among older patients hospitalized for COVID-19 and its association with mortality is unclear. This study aims to investigate the prevalence of hypothyroidism in older COVID-19 inpatients and verify if this comorbidity is associated with a specific pattern of onset symptoms and a worse prognosis. Methods COVID-19 inpatients aged ≥ 60 years, participating in the GeroCovid acute wards cohort, were included. The history of hypothy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(44 reference statements)
1
0
0
Order By: Relevance
“…In this meta-analysis, we systematically examined the effects of SARS-CoV-2 infection on thyroid function. Our overall findings showed that TSH, TT3, and TT4 levels were not significantly affected by SARS-CoV-2 infection, thus aligning with the current popular hypothesis that SARS-CoV-2 infection does not directly induce significant changes in thyroid function (15). However, our findings indicate several relevant effects when we investigated the impact of the severity of COVID-19.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this meta-analysis, we systematically examined the effects of SARS-CoV-2 infection on thyroid function. Our overall findings showed that TSH, TT3, and TT4 levels were not significantly affected by SARS-CoV-2 infection, thus aligning with the current popular hypothesis that SARS-CoV-2 infection does not directly induce significant changes in thyroid function (15). However, our findings indicate several relevant effects when we investigated the impact of the severity of COVID-19.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, there are studies suggesting that COVD-19 may trigger an inflammatory response in the thyroid gland, leading to transient hypothyroidism (13). Nevertheless, these studies do not always converge on a shared conclusion (10)(11)(12)(13)(14)(15)(16). The inconsistency may be due to a variety of factors, such as the differences in biochemical detection methods used, the population characteristics of the subjects, the geographical environment, and the specific genotypes or variants of SARS-CoV-2 involved.…”
Section: Introductionmentioning
confidence: 99%